Analysis of the competitiveness of the tourist destination and the development of the ecuadorian cocoa routes - Salazar Duque, Diego (2022)
Combining certain recreational activities with agricultural production contributes favorably to tourism; for this reason, this research analyzes the competitiveness of the tourist destination and the development of the Ecuadorian cocoa routes. A quantitative approach with a non-experimental, descriptive and cross-sectional design is used to collect information on 9 of the 16 identified tourist routes in Ecuador, where cocoa varieties are grown, especially fine aroma cocoa with denomination of origin. The objective is to analyze the competitiveness of the tourist destination and the development of the Ecuadorian cocoa routes in relation to the factors that contribute to the development of a tourist activity: product, performance, future and support for community tourism and, in this way, to understand the opportunity for tourism and cocoa production growth to be sustainable. There is an imbalance between the evaluated variables that do not favor the destination to reach a level of competitiveness compared to others that offer the same or similar product; in addition, there is a lack of strategies, actions or a monitoring and control process, which does not contribute to tourism development.